Impementasi Metode Talaqqi dalam Pembelajaran Al-Qur’an pada Siswa Sekolah Dasar Islam Terpadu (SDIT) As-Sunnah Kota Baubau - Yuli Rahim; Muhammad Ridwan; Jufri Jufri (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Problems in reading the Qur’an frequently occur, especially among elementary school students who are at the early stages of learning the Qur’an. One of the issues that arises is that students tend to read in a hurried manner and focus only on fluency in pronouncing the letters without paying attention to the rules of mad (elongation). In addition, when reading the Qur’an, the articulation of letters (makhraj al-huruf) is sometimes inaccurate. This study aims to examine how the talaqqi method is implemented in Qur’anic learning among students at SDIT As-Sunnah Baubau City, as well as to identify the advantages and disadvantages of applying the talaqqi method for elementary school students. This research was conducted using a descriptive qualitative method. Data were collected through interviews, observations, and documentation. The results of the study indicate that the talaqqi method is implemented through several stages, including the teacher reciting verses, followed by students listening and directly imitating what the teacher recites. In this implementation, the teacher provides immediate correction of the students’ recitation. The advantages of the talaqqi method lie in the direct interaction between teacher and students, allowing errors to be corrected promptly. Meanwhile, its disadvantages include time limitations, particularly when applied in large classes, making the method less effective due to its dependence on the teacher’s teaching ability.